Identification of HLA-B*13:01 allele in leprosy patients with dapsone hypersensitivity syndrome in Ambon, Indonesia - Menaldi, Sri Linuwih Susetyo Wardhani; Priyanto, Mufqi Handaru; Widaty, Sandra; Irawati, Yunia; Aswin, Yulia Ariani; Suryandari, Dwi Anita; Marissa, Melani; Ariawan, Iwan; Kartika, Emiliana; Yunifananda, Malika Sabrina; Thio, Hok Bing (Frontiers in Tropical Diseases, 2025)
BackgroundIndonesia ranks third globally in leprosy, with the eastern part of the country, particularly Ambon, still reporting high prevalence rates. In Ambon, the capital city of Maluku Province, the prevalence is 8.27 per 10.000 persons, exceeding the national rate of 0.61. While multidrug therapy (MDT) including Dapsone remains the standard treatment for leprosy, it carries the risk of a severe adverse reaction known as Dapsone Hypersensitivity Syndrome (DHS). DHS has been reported in eastern Indonesia, sometimes with fatal outcomes, including in Ambon. Recent research suggests a link between the HLA-B 13*01allele and DHS. Therefore, this study aims to investigate the association between HLA-B*13:01 and DHS within Ambon and surrounding regions.MethodsThis case-control study included leprosy patients undergoing or having completed MDT therapy in Maluku. Cases were included if they met two or more Richardus and Smith’s criteria and were recruited from several hospital in Ambon and Tual Cities. Controls were leprosy patients with >8 weeks of Dapsone exposure without DHS symptoms. Peripheral blood samples were collected, and DNA was extracted from lymphocytes using the QIAGEN QIAmp kit with a modified 2-hour incubation. HLA-B*13:01 genotyping was performed using PCR with specific primers, followed by gel electrophoresis and Sanger sequencing. Statistical analysis was performed using SPSS. Associations between categorical variables were assessed using the Chi-square test, with Fisher’s exact test used when expected cell counts were <5. Significance was set at p<0.05.ResultsA total of 8 cases and 53 controls were included. The HLA-B*13:01 was present in 100% of DHS cases and 6% of controls. Statistical analysis using Fisher’s exact test revealed a significant association between HLA-B*13:01 and DHS (p < 0.001).ConclusionsThis study demonstrates a significant association between HLA-B 13*01 and DHS in Ambon’s leprosy patients. These findings support the potential use of HLA-B*13:01 as a screening tool to identify individuals at high DHS risk before dapsone initiation, potentially improve patient safety by preventing fatal adverse events, optimizing treatment outcomes for leprosy patients by avoiding delayed treatment, and ultimately reducing leprosy transmission rates in Ambon, its surrounding regions, and other high-prevalence areas.